Patient knowledge of HIV and its treatment in South Africa - Lauren M. Terblanche; Ethelwynn L. Stellenberg (AOSIS, 2014)
Background: Patients on antiretroviral therapy (ART) need to achieve a 90% adherence rate to ART in order to prevent disease progression and drug resistance. The patients' knowledge of ART and HIV is thus crucial to ensuring good adherence, decreased risk for drug resistance and cost-effective treatment for these patients. Aim: To determine the knowledge of infected patients with regard to HIV and the ART they were receiving. Setting: The study was conducted at a comprehensive community health centre in a developing low socio-economic community near Cape Town, South Africa. Methods: A quantitative descriptive correlative research design was applied. A sample consisting of 200 (8.5%) respondents was selected from a population of 2349. A multiple-choice questionnaire, comprising 29 questions, including 14 critical knowledge testing questions, was used in individual interviews conducted by either the researcher or fieldworker who assessed the respondents' knowledge regarding various key aspects of HIV and ART. Results: Misconceptions regarding HIV and ART were revealed and scores for the 14 critical knowledge testing questions in the questionnaire revealed that 0% of the respondents had good knowledge, 20% had average knowledge and 80% had poor knowledge. Conclusion: The respondents on ART in this particular community health centre had poor knowledge of HIV and ART. This may contribute to poor adherence rates, increased drug resistance, disease progression and increased costs for the government with regard to treating such patients. Increased attention needs to be given to patient education.